Levocarnitine for pegaspargase‐induced hepatotoxicity in older children and young adults with acute lymphoblastic leukemia. (16th September 2021) - Schulte, Rachael; Hinson, Ashley; Huynh, Van; Breese, Erin H.; Pierro, Joanna; Rotz, Seth; Mixon, Benjamin A.; McNeer, Jennifer L.; Burke, Michael J.; Orgel, Etan
Abstract: Background: Pegaspargase (PEG‐ASP) is an integral component of therapy for acute lymphoblastic leukemia (ALL) but is associated with hepatotoxicity that may delay or limit future therapy. Obese and adolescent and young adult (AYA) patients are at high risk. Levocarnitine has been described as potentially beneficial for the treatment or prevention of PEG‐ASP‐associated hepatotoxicity. Methods: We collected data for patients age ≥10 years who received levocarnitine during induction therapy for ALL, compared to a similar patient cohort who did not receive levocarnitine. The primary endpoint was conjugated bilirubin (c.bili) >3 mg/dl. Secondary endpoints were transaminases >10× the upper limit of normal and any Grade ≥3 hepatotoxicity. Results: Fifty‐two patients received levocarnitine for prophylaxis ( n = 29) or rescue ( n = 32) of hepatotoxicity. Compared to 109 patients without levocarnitine, more patients receiving levocarnitine were obese and/or older and had significantly higher values for some hepatotoxicity markers at diagnosis and after PEG‐ASP. Levocarnitine regimens varied widely; no adverse effects of levocarnitine were identified. Obesity and AYA status were associated with an increased risk of conjugated hyperbilirubinemia and severe transaminitis. Multivariable analysis identified a protective effect of levocarnitine on the development of c.bili >3 mg/dl (OR 0.12, p = 0.029). There was no difference between groups in CTCAE Grade ≥3 hepatotoxicity. C.bili >3 mg/dl during induction was associated with lower event‐free survival. Conclusions: This real‐world data on levocarnitine supplementation during ALL induction highlights the risk of PEG‐ASP‐associated hepatotoxicity in obese and AYA patients, and hepatotoxicity's potential impact on survival. Levocarnitine supplementation may be protective, but prospective studies are needed to confirm these findings. Abstract : Patients who are adolescents or young adults and/or who are obese are at higher risk for pegaspargase‐induced hepatotoxicity. Levocarnitine supplementation may reduce the risk for hepatoxicity during induction therapy for acute lymphoblastic leukemia.